Guided Math : a Framework for Mathematics Instruction - Sammons, Laney (Guided math series., 2019)
This 2nd edition takes an innovative approach to mathematics, using the same teaching philosophies as guided reading. This instructional framework provides an environment for math that fosters mathematical thinking and meets the needs of all students.